2010
DOI: 10.4049/jimmunol.1000798
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-101 Targets MAPK Phosphatase-1 To Regulate the Activation of MAPKs in Macrophages

Abstract: MAPK phosphatase-1 (MKP-1) is an archetypical member of the dual-specificity phosphatase family that deactivates MAPKs. Induction of MKP-1 has been implicated in attenuating the LPS- or peptidoglycan-induced biosynthesis of proinflammatory cytokines, but the role of noncoding RNA in the expression of the MKP-1 is still poorly understood. In this study, we show that MKP-1 is a direct target of microRNA-101 (miR-101). Transfection of miR-101 attenuates induction of MKP-1 by LPS as well as prolonged activation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
107
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(116 citation statements)
references
References 58 publications
8
107
1
Order By: Relevance
“…17,18 Previous studies demonstrated that expression of miR-101a is modulated by the PI3K/Akt signaling pathway, which is activated in response to IL-1β. 19,20 Wei et al 21 have demonstrated that miR-30b is positively regulated by NF-κB. Therefore, we believe that IL-1β alone is capable of inducing alterations in miR-101a and miR-30b expression, and that IL-1β-mediated signaling pathways participate in the induction of miR-101a and miR-30b in β-cells, though the latter hypothesis requires further investigation.…”
Section: Discussionmentioning
confidence: 74%
“…17,18 Previous studies demonstrated that expression of miR-101a is modulated by the PI3K/Akt signaling pathway, which is activated in response to IL-1β. 19,20 Wei et al 21 have demonstrated that miR-30b is positively regulated by NF-κB. Therefore, we believe that IL-1β alone is capable of inducing alterations in miR-101a and miR-30b expression, and that IL-1β-mediated signaling pathways participate in the induction of miR-101a and miR-30b in β-cells, though the latter hypothesis requires further investigation.…”
Section: Discussionmentioning
confidence: 74%
“…Instead, a slight yet significant reduction in IRAK-M occurs after 2 h of super low dose LPS treatment. Other negative regulatory pathways induced by high dose LPS include the PI3K pathway that contributes to the suppression of IRAK-1/ TNF receptor-associated factor 6 (22), the induction of negative regulators, including IRAK-M (25,31), and the induction of negative transcriptional suppressors of inflammatory genes such as RelB and cAMP response element-binding (32,33). Thus, we tested the effects of super low dose LPS on the activation status of PI3K pathway.…”
Section: Super Low Dose Lps Primes Whereas High Dose Lps Tolerizes mentioning
confidence: 99%
“…For example, IB␣ suppresses p65/RelA by secluding it in the cytoplasm; MAPK phosphatase 1 suppresses the activities of MAP kinases (20); IRAK-M suppresses interleukin receptor-associated kinase 1 (IRAK-1) (21); and RelB blocks the transcription of proinflammatory mediators by assembling a suppressive complex on their promoters (19). In addition, LPS is known to activate the phosphoinositide 3-kinase (PI3K) pathway, which dampens the expression of proinflammatory mediators through inducing negative regulators, including MAPK phosphatase 1, IRAK-M, and suppressing IRAK-1 (22)(23)(24)(25)(26). As a consequence, LPS (Ͼ1 ng/ml) causes a robust yet transient expression of proinflammatory media-tors, followed by a refractory tolerant state.…”
mentioning
confidence: 99%
“…Raf kinase inhibitory protein suppresses a cascade of metastasis signalling involving LIN28 and let-7 [65]. Zhu and his colleagues found that miR-101 targets MAPK phosphatase 1 to regulate the activation of MAPKs in macrophages [66]. MiR-146a suppresses tumor growth and progression by targeting EGFR pathway and in a p-ERK-dependent manner in castration-resistant prostate cancer [67].…”
Section: Mapk Pathwaymentioning
confidence: 99%